Expression, purification, crystalization and preliminary X-ray analysis of cyclophilin A from the bovine parasite Trypanosoma brucei brucei - Dao-Thi, M.H.; Transue, T.R.; Pelle, Roger; Murphy, N.B.; Poortmans, F.; Steyaert, J. (1998)
Cyclophilin A from the bovine parasite Trypanosoma brucei brucei has been cloned, expressed in Escherichia coli, purified and crystallized in the presence of cyclosporin A using ammonium sulfate as a precipitant. The crystals belong to the orthorhombic crystal system with unit-cell dimensions of a=118.61, b=210.15 and c=153.21 A. A data set complete to 2.7 A has been collected using rotating-anode radiation. However the crystals diffract to at least 2.1 A resolution using synchrotron radiation.